2020
DOI: 10.3390/cancers12092679
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy for Stage III Colon Cancer

Abstract: In patients with stage III colon cancer (CC), adjuvant chemotherapy with the combination of oxapliplatin to a fluoropyrimidine (FOLFOX or CAPOX) is a standard of care. The duration of treatment can be reduced from 6 months to 3 months, depending on the regimen, for patients at low risk of recurrence, without loss of effectiveness and allowing a significant reduction in the risk of cumulative sensitive neuropathy. However, our capacity to identify patients that do really need this doublet adjuvant treatment rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 99 publications
1
36
0
1
Order By: Relevance
“…The current stage of CRC is classified based on the tumor-node-metastasis (TNM) system issued by the American Joint Committee on Cancer (AJCC), which is routinely standard for the prognostic management and determination of adjuvant chemotherapy (ACT) of early-stage CRC [ 2 ]. After surgery, ACT is a conventional therapy for stage III and a subset of stage II CRC patients (eg, high grade, T4) [ 3 , 4 ]. The goal of ACT is to eradicate residual cancer cells after surgical resection, thus reducing the recurrence rate or extending the time to recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The current stage of CRC is classified based on the tumor-node-metastasis (TNM) system issued by the American Joint Committee on Cancer (AJCC), which is routinely standard for the prognostic management and determination of adjuvant chemotherapy (ACT) of early-stage CRC [ 2 ]. After surgery, ACT is a conventional therapy for stage III and a subset of stage II CRC patients (eg, high grade, T4) [ 3 , 4 ]. The goal of ACT is to eradicate residual cancer cells after surgical resection, thus reducing the recurrence rate or extending the time to recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…CRC is commonly treated by surgery; however, up to half of patients diagnosed with early-stage CRC experience recurrent disease after a surgical resection and may also develop a metastatic disease. As such, neoadjuvant and adjuvant therapies have a crucial role against CRC [ 2 ]. These include chemotherapy, radiotherapy, interventional therapy, and biotherapy [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, neoadjuvant and adjuvant therapies have a crucial role against CRC [ 2 ]. These include chemotherapy, radiotherapy, interventional therapy, and biotherapy [ 2 , 3 ]. Unfortunately, systemic toxic effects, which impair the patient quality of life, and the development of resistance during therapy limit the long-term efficacy of these therapeutic approaches, especially in metastatic cases.…”
Section: Introductionmentioning
confidence: 99%
“…Even with radical surgery, the postoperative recurrence rate with stage III colon cancer is still as high as 50-80% (3). Previously published studies have found that adjuvant chemotherapy could reduce the risk of recurrence and improve survival for patients stage III colon cancer (4). Therefore, adjuvant chemotherapy is routinely recommended for stage III colon cancer for 6 months following surgery by the National Comprehensive Cancer Network (5).…”
Section: Introductionmentioning
confidence: 99%